Penggunaan Batu Sungai Seriti Kabupaten Luwu pada Campuran AC-BC - Valentine Mangetan; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2021)
Technology Development and Innovation in the Revolutionary Era 4.0 is needed, especially in innovating the use of local materials. The Seriti River material in Lamasi Timur Subdistrict, Luwu Regency, has great potential if it is used as material in road pavements, but until now these materials have been used only to build residential houses for local communities. The purpose of this study was to test the characteristics of the material, to analyze the AC-BC mixture using material from the Seriti river, Luwu Regency with variations in asphalt content of 5.00% 5.50% 6.00% 6.50% and 7.00% and to determine the resistance of the mixture. against temperature and water immersion with the Marshall Time Stability test. The results showed that the characteristics of the aggregate originating from the Seriti River, Luwu Regency, meet the specification standard as an AC_BC material. The composition design of the AC-BC mixture obtained the proportion of coarse aggregate 42.82%, thirsty aggregate 45.73%, filler 5.45% with optimum aspaI content of 6.00%. In this study, the Seriti River aggregate of Luwu Regency was used in the AC-BC mixture so that the aggregate characteristics must be known first. The characteristics of coarse aggregate, fine aggregate, asphalt and filler must meet the requirements contained in the General Specifications of Bina Marga 2018, therefore a series of Characteristics tests were carried out before designing the composition of the AC-BC mixture for the manufacture of AC-BC mixture test specimens. The test object will then be tested by Marshall to determine the characteristics of the AC-BC mixture. Through the MarshalI Immertion test, the residual MarshalI stability results were 96.61% with an aspiration level of 6.00%.